2012
DOI: 10.1093/infdis/jis186
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection During Pregnancy With Maternofetal Transmission Induces a Proinflammatory Cytokine Bias in Placenta and Amniotic Fluid

Abstract: Congenital infection with cytomegalovirus (CMV) can induce immune responses and placental damage. By use of immunoassay panels, 27 cytokines were assessed in midtrimester amniotic fluid from 8 patients with congenital CMV, in midtrimester sera from 12 pregnant women with primary CMV infection, and in amniotic fluid and serum from uninfected maternal controls. Levels of the cytokines tumor necrosis factor α, interleukin 1β, interleukin 12, and interleukin 17; the chemokines CCL2, CCL4, and CXCL10; and the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 15 publications
8
47
0
Order By: Relevance
“…When expression of chemokines is compared between infected and transfected HUVEC, quite a few more chemokines could be detected in infected cells, supporting previous studies of upregulation of growth factors/chemokine/cytokines following HCMV infection (Frascaroli et al, 2006;Hamilton et al, 2012;Li et al, 2014;Murayama et al, 1997;Scott et al, 2012;Smith et al, 2014;Weseslindtner et al, 2014). Indeed, we found 18 chemokines elevated in HCMV-infected HUVEC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When expression of chemokines is compared between infected and transfected HUVEC, quite a few more chemokines could be detected in infected cells, supporting previous studies of upregulation of growth factors/chemokine/cytokines following HCMV infection (Frascaroli et al, 2006;Hamilton et al, 2012;Li et al, 2014;Murayama et al, 1997;Scott et al, 2012;Smith et al, 2014;Weseslindtner et al, 2014). Indeed, we found 18 chemokines elevated in HCMV-infected HUVEC.…”
Section: Discussionsupporting
confidence: 90%
“…HCMV infection has been associated with poor placentation and foetal outcome. Placentas showing productive HCMV infection have shown altered significant modulation of host cytokines (Hamilton et al, 2012;Scott et al, 2012) although the contribution of viral factors have not been determined.…”
Section: Chapter 3 -Hcmv Vgpcr Effects Upon Human Cell Types 31 Intrmentioning
confidence: 99%
“…27 Understanding the basis for persistent infection in AmEpCs could lead to therapeutic strategies to prevent congenital disease and pregnancy complications by targeting viral functions that promote persistence and enhancing host antiviral responses that suppress infection.…”
Section: Hcmv Persistent Hcmv Infection In the Amnionmentioning
confidence: 99%
“…26 Analysis of amniotic fluid from cases of congenital HCMV infection showed elevated levels of inflammatory cytokines and chemokines, suggesting inflammatory responses could contribute to pathology. 27 We recently reported that epithelial cells in amniotic membranes from pregnancies complicated by congenital HCMV infection and IUGR contain viral proteins in large cytoplasmic vesicles. 6 Herein, we examined 51 placentas from deliveries that included congenital infection diagnosed by the detection of viral DNA in amniotic fluid and/or newborn saliva, idiopathic preterm deliveries, IUGR, and gestational age-matched controls.…”
mentioning
confidence: 99%
“…A case control study of association between ZIKV and microcephaly showed ZIKV present in mothers of 24/32 cases of microcephaly compared with 39/61 mothers of controls (p = 0.12), and that in the babies, 13/32 with microcephaly compared with 0/16 of the controls had ZIKV infection 4 . These rates compare with rates of MTCT in maternal cytomegalovirus (CMV) infection of 32% in primary infection and 1.4% during reactivation 5 , and for rubella of 80% to 25%, depending upon gestation 6 . Effects on the fetus for all these infections depend upon many factors, including maternal immunity, gestation of infection, and viral characteristics.…”
Section: Clinical Outcomes Of Mother To Child Transmission and Diagnomentioning
confidence: 99%